Identitas Sastra Arab Kontemporer dan Perubahan Ekonomi - Luhuringbudi, Teguh (Alfaz (Arabic Literatures for Academic Zealots), 2018)
This study proves that Arabic as an identity and as a connector between the contemporary Arabic literary products and economic changes. It can be concluded that the more faded the use of Arabic, the various Arabic cultural and literary products will be degraded and even eliminated; and the magnitude of the value of economic changes that cannot be detailed will be a deficit, especially in the field of creative industry and translation. This research is aimed to explore the significance and relevance of cultural products to the East-an. This research uses library method in the perspective of data gathering and qualitative method in data reduction perspective. The perspective used is the perspective of globalization. Stages of analysis related perspectives used are the placement of the global arena, symbiotic mutualism, and technological involvement.